Study of design and manufacturing process of proton exchange membrane fuel cell : catalyst coated membrane - Devika Vijay Shinde (2013)
The whole world needs energy to run on. Energy has drastically improved the quality of life of modern society and allowed the rapid advancement of modern technology. The energy needs of the world today are met largely by fossil fuels that emit greenhouse gases among other pollutants. Apart from the environmental damage they cause, these fossil fuels are limited and fast depleting and hence, alternate sources of energy are being explored. Fuel cells offer a promising solution to this problem.